Information and Communication Technology for Intelligent Systems Proceedings of ICTIS 2018, Volume 1 - Satapathy, Suresh Chandra; Joshi, Amit (Smart Innovation, Systems and Technologies,, 2019)
The book gathers papers addressing state-of-the-art research in all areas of Information and Communication Technologies and their applications in intelligent computing, cloud storage, data mining and software analysis. It presents the outcomes of the third International Conference on Information and Communication Technology for Intelligent Systems, which was held on April 6-7, 2018, in Ahmedabad, India. Divided into two volumes, the book discusses the fundamentals of various data analytics and algorithms, making it a valuable resource for researchers' future studies. .